Development of context-based interactive PowerPoint media to enhance junior high school students’ mathematical problem-solving skills - Seli Razna Helia; Ana Setiani; Pujia Siti Balkist; Dadan Rahmat (Universitas Sarjanawiyata Tamansiswa, 2026)
This study aimed to develop context-based interactive PowerPoint media and to evaluate its validity, practicality, and the outcomes of its implementation for junior high school students’ mathematical problem-solving skills. The study employed the Research and Development (R&D) method, adapting the ADDIE development model. The product was evaluated through implementation with a single group using a one-group pretest–posttest design without a control group, involving 30 seventh-grade students of Class VII-C at SMP Negeri 2 Takokak. Data were collected using validation sheets completed by subject-matter and media experts, practicality questionnaires distributed to teachers and students, and mathematical problem-solving tests administered at the pretest and posttest stages. The developed media obtained validity ratings of 97.58% from subject-matter experts and 91.67% from media experts, placing it in the “highly valid” category. Practicality was confirmed by very positive teacher responses of 97.62%, while student responses reached 83.85% in the small-group test and rose to 88.72% in the field test, indicating that the media is very practical. Implementation was also accompanied by an improvement in students’ mathematical problem-solving skills, as shown by an increase in the mean score from 49.85 to 89.69, a 100% mastery rate, and an N-Gain of 0.80, which falls into the “high” category. Based on the results of the Wilcoxon Signed-Rank Test, all students achieved higher posttest scores compared to their pretest scores (Positive Ranks = 30; Negative Ranks = 0). Because the evaluation involved only one group without a control group, the findings indicate an improvement in mathematical problem-solving skills following implementation of the media, but they cannot yet establish a cause-and-effect relationship. Overall, the context-based interactive PowerPoint media developed in this study demonstrates a very high level of validity and practicality, and its implementation was followed by an increase in students’ mathematical problem-solving skills.